Analisis Perbandingan Metode SAW (Simple Additive Weighting), WP (Weight Product) dan SMART (Simple Multi Attribute Rating Technique) Untuk Pemilihan Domba Kurban - M Lutfi MA; Kapti; Yeza Febriani (JSAI (Journal Scientific and Applied Informatics), 2024)
In implementing urban worship, it is often difficult for shohibul qurban to determine the quality of urban animals because it has several criteria/requirements that must be met so that the animals are sacrificed according to sharia. This study aims to analyze the decision support system method for selecting qurban animals using the SAW (Simple Additive Weighting), WP (Weight Product), and SMART (Simple Multi-Attribute Rating Technique) methods. The results showed that the WP method has an accuracy rate of 99.998% so this method is the most feasible to use for the selection of sacrificial sheep when compared to the SMART and SAW methods with the calculation results in the level of suitability at 99.994% for the SAW method and 99.876% for the SMART method. Sheep 4 has the highest weight ranking of other sheep in all methods, scoring 0.923 in the SAW method, 0.1727 in the WP method, and 17.8 in the SMART method. Sheep 4 criteria is the ideal criteria for a sacrificial animal.